2010
DOI: 10.1115/1.4001968
|View full text |Cite
|
Sign up to set email alerts
|

CFD Evaluation of Solid Particles Erosion in Curved Ducts

Abstract: This paper investigates numerically the erosion phenomenon that occurs in 90 deg and 180 deg curved ducts. The erosion prediction model comprises from three stages: flow modeling, particle tracking, and erosion calculations. The proposed three stages of the present model are tested and validated. Comparisons between predicted penetration rate and published experimental data show a good agreement. The effects of bend orientation, inlet gas velocity, bend dimensions, loading ratio, and particle size on the penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…It was suggested that the erosion is mostly dependent on the ratio of curvature and initial velocity [3,4]. Other studies also considered angle of impacting particles on the erosion rate [5]. In our case the angle is 0 0 as the flow is along the surface of material.…”
Section: Introductionmentioning
confidence: 83%
“…It was suggested that the erosion is mostly dependent on the ratio of curvature and initial velocity [3,4]. Other studies also considered angle of impacting particles on the erosion rate [5]. In our case the angle is 0 0 as the flow is along the surface of material.…”
Section: Introductionmentioning
confidence: 83%
“…The grid is selected based on grid independence study for each case and the dimensionless wall distance, y+ is less than unity in all the tested cases. The FORTRAN code used in the present study was originally developed by ElBehery et al (2009) to simulate gas-solid flow in curved ducts and to predict the erosion rate in such geometries (El-Behery et al, 2010). In the present study the code is further modified by including the particle-particle collision, wall roughness, particleturbulence interaction and heat transfer.…”
Section: Solution Proceduresmentioning
confidence: 98%
“…where b, c, d 1 , d 2 , d 3 , and d 4 are empirical constants for the E/CRC model, which are listed in Table 1. 19,20 The Hertz-Mindlin with Archard wear model estimates the depth of erosion on a wall surface, and it primarily addresses the effects of abrasive erosion and low-angle impact on a wall due to tangential collisions between solids and the wall. 21 The Archard equation is expressed as…”
Section: Erosion Modelmentioning
confidence: 99%